2022
DOI: 10.1007/s00415-022-11433-z
|View full text |Cite|
|
Sign up to set email alerts
|

Motor, cognitive and behavioural profiles of C9orf72 expansion-related amyotrophic lateral sclerosis

Abstract: Introduction Amyotrophic lateral sclerosis (ALS) individuals carrying the hexanucleotide repeat expansion (HRE) in the C9orf72 gene (C9Pos) have been described as presenting distinct features compared to the general ALS population (C9Neg). We aim to identify the phenotypic traits more closely associated with the HRE and analyse the role of the repeat length as a modifier factor. Methods We studied a cohort of 960 ALS patients (101 familial and 859 sporadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
1
16
3
Order By: Relevance
“…A number of studies have found a reduced survival time in patients with C9pALS compared with C9nALS,4 6–9 12 13 15 17 18 while others did not 10 19. When compared with patients carrying other ALS-causing mutations, C9ORF72 gene carriers had a similar survival time to patients who were SOD1 positive (median 3.2 and 3.8 years, respectively), with shorter survival time for FUS carriers (median 1.9 years) and longer for TARDBP carriers (median 5.0 years) 5.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…A number of studies have found a reduced survival time in patients with C9pALS compared with C9nALS,4 6–9 12 13 15 17 18 while others did not 10 19. When compared with patients carrying other ALS-causing mutations, C9ORF72 gene carriers had a similar survival time to patients who were SOD1 positive (median 3.2 and 3.8 years, respectively), with shorter survival time for FUS carriers (median 1.9 years) and longer for TARDBP carriers (median 5.0 years) 5.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have found variations in the phenotype of patients with C9ORF72 gene-positive ALS (C9pALS) compared with C9ORF72 gene-negative ALS (C9nALS). In particular, there is a greater prevalence of cognitive impairment 4–13. Other aspects of the C9pALS phenotype are less well defined however.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations